Performance analysis of Paralympic 2.4mR class sailing - Caraballo, I.; Cruz-Leon, C.; Pérez-Bey, A.; Gutiérrez-Manzanedo, J. V. (Journal of Sports Sciences, 2021)
Adapted sailing is a Paralympic sport in which sailors with different types of disabilities can compete in the same event. According to 2.4mR Class, eligible impairments include limb deficiency and vision impairment. However, it is still unknown the variables that determine performance. Thus, the objectives of this study were: (i) to identify the variables that determine the sailing performance, (ii) to analyse the influence of the type of impairment on sailing performance, and (iii) analyse the influence of the wind force on sailing performance. Thirty-three elite sailors with disabilities participated and were divided into three groups according to the type of impairment: affectation of upper, lower, or upper and lower limbs. Participants were evaluated during three 2.4mR class World Cups and the following variables were assessed: velocity made good, distance and manoeuvres in upwind-downwind courses and type of impairment. Those sailors with better performance travelled a shorter distance during downwind sailing. The results showed that performance was not affected by which category the sailor was placed according to the type of impairment. The sailors with a lesser disability perform better when the wind is medium and high.